El género Jaltomata Schltdl. (Solanaceae) en la región La Libertad y un nuevo taxón del Norte de Perú - González, Segundo Leiva; Mione, Thomas; Yacher, Leon (Arnaldoa, 2017)
0 citations (Crossref) [2023-10-31] Citation Key Alias: pop00298 tex.type: [object Object]
Keywords: dept.egm

Especies de jaltomata schltdl. (solanaceae) con néctar rojo, tres nuevas combinaciones nomenclaturales y un nuevo taxón del noreste de perú - Gonzalez, Segundo Leiva; Mione, Thomas; Yacher, Leon (Arnaldoa, 2016)
Citation Key Alias: lens.org/148-203-876-064-621 tex.type: [object Object]
Keywords: dept.egm; ⚠️ Invalid DOI

Jaltomata athahuallpae (solanaceae), una nueva especie del norte del perú - González, Segundo Leiva; Mione, Thomas; Yacher, Leon (Arnaldoa, 2015)
Citation Key Alias: pop00375 tex.type: [object Object]
Keywords: dept.egm; ⚠️ Invalid DOI

Jaltomata angasmarcae y jaltomata pauciseminata (solanaceae), dos nuevas especies del norte del perú - Gonzalez, Segundo Leiva; Mione, Thomas; Yacher, Leon (Arnaldoa, 2015)
Citation Key Alias: lens.org/107-286-838-809-425 tex.type: [object Object]
Keywords: dept.egm; ⚠️ Invalid DOI

Jaltomata glomeruliflora (Solanaceae) una nueva especie del Norte de Perú - González, Segundo Leiva; Mione, Thomas; Yacher, Leon (Arnaldoa, 2015)
Citation Key Alias: pop00377 tex.type: [object Object]
Keywords: dept.egm; ⚠️ Invalid DOI

Jaltomata anteropilosa (Solanaceae) una nueva especie del Norte de Perú - González, Segundo Leiva; Mione, Thomas; Yacher, Leon (Arnaldoa, 2015)
Keywords: dept.egm; ⛔ No DOI found

Jaltomata parviflora (Solanaceae) una nueva especie del Norte del Perú - González, Segundo Leiva; Mione, Thomas; Yacher, Leon (Arnaldoa, 2010)
Citation Key Alias: pop00185 tex.type: [object Object]
Keywords: dept.egm; ⛔ No DOI found

Two new Peruvian species of Jaltomata (Solanaceae, Solaneae) with red floral nectar - Mione, Thomas; González, Segundo Leiva; Yacher, Leon (Brittonia, 2014)
Two new Jaltomata species (Solanaceae) of Peru that produce red floral nectar are described. Jaltomata neei of Department Cajamarca has 1–4 flowers per inflorescence, the campanulate corolla is green and then changes to blue, corolla lobes (5) and lobules (5) are equally prominent, a corona is lacking, five radial staminal-corolla thickenings create nectar troughs between, and the stigma is capitate. Jaltomata quipuscoae of Department Arequipa has solitary flowers, a purple, broadly crateriform, 5-lobed corolla, a corona on which nectar pools, a punctiform stigma, lacks corolla thickenings, and the mature fruit is whitish. Photographs, illustrations and tables are included that allow comparison with closely related species. © 2014, The New York Botanical Garden.
10 citations (Crossref) [2023-10-31] Citation Key Alias: pop00141 tex.type: [object Object]
Keywords: Arequipa; Cajamarca; Jaltomata neei; Jaltomata quipuscoae; Peru; corolla color change; corona; dept.egm; lomas; protogyny; red nectar

Transfer of saracha weberbaueri dammer subspecies pallascana bitter, also known as saracha pallascana (bitter) macbride, to jaltomata pallascana (bitter) mione (solanaceae) - Mione, Thomas; Gonzalez, Segundo Leiva; Yacher, Leon (Arnaldoa, 2008)
Citation Key Alias: lens.org/153-726-006-094-847 tex.type: [object Object]
Keywords: dept.egm; ⛔ No DOI found

Tres nuevas especies de jaltomata schlechtendal (solanaceae) del norte del perú - Gonzalez, Segundo Leiva; Mione, Thomas; Yacher, Leon (Arnaldoa, 2006)
Citation Key Alias: lens.org/106-602-833-031-752 tex.type: [object Object]
Keywords: dept.egm; ⛔ No DOI found

Five new species of jaltomata (solanaceae) from cajamarca, peru - Mione, Thomas; Leiva, G Segundo; Yacher, Leon (Novon, 2007)
Five new suffrutescent to shrubby Jaltomata Schlechtendal species (Solanaceae) of the department of Cajamarca, Peru, are described and illustrated, Jaltomata contumacensis S. Leiva & Mione has a light green, urceolate-tubular corolla and grows in the province of Contumazá between 2530 and 3000 m; J. lanata S. Leiva & Mione has a whitish purple to pale purple, short-tubular corolla and grows in the province of San Pablo between 1850 and 2400 m; J. leivae Mione has a red-violet, urceolate corolla containing red nectar and grows in the province of Contumazá between 2560 and 2650 m; J. oppositifolia S. Leiva & Mione bas a white, broadly infundibular to rotate corolla and grows in province Chota between 2250 and 3090 m; and J. yacheri Mione & S. Leiva has a blue-purple, urceolate corolla and grows in province Hualgayoc at 3460 m. The fruits of two of these species are eaten by people.
5 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/001-566-646-221-355 tex.type: [object Object]
Keywords: Edible fruit; Jaltomata; Magnoliophyta; Red nectar; Solanaceae; dept.egm

Red nectar presentation and characterization of the breeding system of an Andean nightshade - Mione, Thomas; Cotton, Anna C.; Leiva González, Segundo; Yacher, Leon I. (Plant Biosystems - An International Journal Dealing with all Aspects of Plant Biology, 2022)
Flowers of Jaltomata weigendiana (Solanaceae) secrete red nectar that is visible through the partially translucent corolla. We report the pattern of nectar presentation during the sexual phases of the flower and characterize the breeding system. Comparison of flower sets experiencing daily removal starting Day 1 with flowers that accumulated nectar for one or two days prior to daily removal revealed no discernible effect on the life-of-the-flower nectar production, sugar production and floral longevity. Flowers produce about the same cumulative volume of nectar during the two sexual phases. However, cumulative nectar sugar production is about 4 times higher during the male phase. Nectar standing crop ranged from 4–26.6 µl for Day 1 flowers and 0–8.7 µl for flowers from which nectar was removed the previous day. With daily removal of nectar, 21 of 40 flowers contained no nectar during the last day of the flower’s life. All unmanipulated flowers developed fruits (autonomous self-pollination). However, manual self-pollinations and manual cross-pollinations resulted in fruits that weighed significantly more and had significantly more seeds than fruits produced by autonomous self-pollination. Protogyny and herkogamy promote cross-pollination, but delayed autonomous selfing at the end of the flower’s life ensures seed set if pollinator-mediated pollination fails.
2 citations (Crossref) [2023-10-31] _eprint: https://doi.org/10.1080/11263504.2022.2100499
Keywords: Autonomous self-pollination; Jaltomata; Solanaceae; colored nectar. edible fruit; dept.egm; floral longevity; peer-reviewed; protogyny; red nectar